ANALYSIS OF THE INFLUENCE OF PRODUCT QUALITY, PROMOTION, BRAND IMAGE AND LIFESTYLE ON PURCHASE DECISION OF MOTORCYCLE KAWASAKI KLX 150CC AT PT. GREENTECH CAKRAWALA MOTORINDO IN PEKANBARU - Sarli Rahman; Agustinus Wijaya (Institut Bisnis dan Teknologi Pelita Indonesia, 2021)
This study aims to determine and analyze the effect of product quality, promotion, brand image and lifestyle on purchasing decisions of the Kawasaki KLX 150cc motorcycle PT. Greentech Cakrawala Motorindo in Pekanbaru. The data used in this study are primary data obtained from questionnaires. Respondents from this study were 150 respondents who visited the Kawasaki Greentech Dealer. The data analysis technique used is multiple linear regression analysis using the t test and F test for hypothesis testing. The results of this study indicate that not all variables have an effect, the product quality and brand image variables have no effect, while the promotion and lifestyle variables have an influence on the purchase decision of the 150cc KLX Kawasaki PT. Greentech Cakrawala Motorindo. Of the four variables, the promotion and lifestyle variables had the most dominant influence on the purchase decision of the 150cc KLX Kawasaki PT. Greentech Cakrawala Motorindo.